Pattern of Sprawl Development Along The Abuja – Keffi Highway Corridor in The North Central Nigeria - Jibrin, Sabo; Junaid, Asimiyu M; Musa , Haruna D (Amcolabora, 2024)
The rapid expansion of urban areas worldwide is widely attributed to the growth of urban populations. The objective of this study is to examine the expansion of urban sprawl in the North Central area of Nigeria, specifically along the Abuja-Keffi highway corridor, over 29 years, from 1991 to 2020. The study utilized satellite imagery from three distinct spatiotemporal intervals (1991–2003, 2003–2015, and 2015–2020) and incorporated three different types of Landsat sensors, namely Enhanced Thematic Mapper (ETM), Enhanced Thematic Mapper Plus (ETM+), and Operational Land Imager (OLI). The study employed image processing and land use classification analysis techniques to generate land use and land cover (LULC). The analysis of the data reveals that there has been a significant increase in sprawling development along the Abuja-Keffi highway corridor. The built-up area of the region has undergone significant expansion over the past three decades, with the urbanized land area increasing from 1081.98 hectares (4.96%) in 1991 to 10263.15 hectares in 2020, accounting for 47.06% of the total built-up area. The research also documented two distinct forms of urban growth, specifically linear and leapfrog, throughout the corridor. The research recommends regional urban policy, urban growth boundaries as well as effective and efficient development control mechanisms in the selected settlements along the corridor. The Abuja Municipal Area Council and Karu Local Government are urged to promote urban renewal and infrastructure development through private partnerships, sustainable policies, waste management systems, and community engagement.